A global phase II randomized trial comparing oral taxane ModraDoc006/r to intravenous docetaxel in metastatic castration resistant prostate cancer - Vaishampayan, Ulka N; Keessen, Marianne; Dreicer, Robert; Heath, Elisabeth I; Buchler, Tomas; Árkosy, Péter F; Csöszi, Tibor; Wiechno, Pawel; Kopyltsov, Evgeny; Orlov, Sergey V; Plekhanov, Alexey; Smagina, Maria; et al. (European journal of cancer, 2024)
STUDY AIM: ModraDoc006, an oral formulation of docetaxel, is co-administered with the cytochrome P450-3A4 and P-glycoprotein inhibitor, ritonavir (r): ModraDoc006/r. The preliminary efficacy and safety of oral ModraDoc006/r was evaluated in a global randomized phase II trial and compared to the current standard chemotherapy regimen of intravenous (i.v.) docetaxel and prednisone. METHODS: 103 mCRPC patients, chemotherapy-naïve with/without abiraterone and/or enzalutamide pretreated, with adequate organ function and evaluable disease per RECIST v1.1 and PCWG3 guidelines were randomized 1:1 into two cohorts. In Cohort 1, 49 patients received docetaxel 75 mg/m2 i.v. every 3 weeks (Q3W). In Cohort 2, 52 patients received ModraDoc006/r; 21 patients with a starting dose of ModraDoc006 30 mg with ritonavir 200 mg in the morning and ModraDoc006 20 mg with ritonavir 100 mg in the evening (30-20/200-100 mg) bi-daily-once-weekly (BIDW) on Days 1, 8, and 15 of a 21-day cycle. To alleviate tolerability, the starting dose was amended to ModraDoc006/r 20-20/200-100 mg in another 31 patients. All patients received prednisone 10 mg daily. Primary endpoint was rPFS. RESULTS: There was no significant difference in rPFS between the 2 arms (p = 0.1465). Median rPFS was 9.5 months and 11.1 months (95% CI) for ModraDoc006/r and i.v. docetaxel, respectively. Partial response was noted in 44.1% and 38.7% measurable disease patients, and 50% decline of PSA was seen in 23 (50%) and 26 (56.5%) evaluable cases treated with ModraDoc006/r and i.v. docetaxel, respectively. The safety profile of ModraDoc006/r 20-20/200-100 mg dose was significantly better than i.v. docetaxel, with mild (mostly Grade 1) gastrointestinal toxicities, no hematologic adverse events, and neuropathy and alopecia incidence of 11.5% and 25%, respectively. CONCLUSIONS: ModraDoc006/r potentially represents a widely applicable, convenient, effective, and better tolerated oral taxane therapy option for mCRPC. Further investigation of ModraDoc006/r in a large randomized trial is warranted.
Keywords: prostatický specifický antigen; prednison; docetaxel; Prostatic Neoplasms, Castration-Resistant; výsledek terapie; přemostěné cyklické sloučeniny; lidé; Docetaxel; Treatment Outcome; Prednisone; Taxoids; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; Prostate-Specific Antigen; Male; Bridged-Ring Compounds; ritonavir; nádory prostaty rezistentní na kastraci; mužské pohlaví; taxoidy; Ritonavir; Humans